Study on Reasons for Employee Attrition in the BPO Sector in NCR Gurgaon EXL PVT LTD: Investigating the Causes and Solutions for Employee Attrition in the BPO Sector (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The wide goal of this examination is to distinguish the underlying drivers of steady loss and maintenance in BPOs, dissecting the level of worker inspiration, fulfillment and inclusion, create a model for boosting sustenance of representatives in the association and concoct solid proposals, which will inevitably be significant to the associations to hold their workers for a long haul.